Randomized Trial Comparing Preliminary Results of Radialization and Centralization Procedures in Bayne Types 3 and 4 Radial Longitudinal Deficiency. Issue 9 (October 2020) - Mittal, Samarth; Garg, Bhavuk; Mehta, Nishank; Kumar, Vijay; Kotwal, Prakash
Abstract : Background: The choice of surgical procedure in severe (Bayne and Klug types 3 and 4) radial longitudinal deficiency (RLD) is contentious. Existing studies have reported varying results with both centralization and radialization procedures. The purpose of this study was to compare the clinical and radiologic outcome of radialization and centralization procedures at a short-to-intermediate–term follow-up for the treatment of types 3 and 4 RLD. Methods: Fourteen patients with 17 affected limbs having types 3 or 4 RLD were recruited in this prospective, randomized, controlled trial. After initial application of successive casts for soft tissue distraction, patients were randomized to 2 wrist alignment procedures—centralization and radialization. Clinical and radiologic parameters recorded at stipulated intervals until a final follow-up of 24 months included hand-forearm angle, ulnar bow, forearm length, arm length, total angulation, and range of motion at elbow, wrist, and fingers. Results: Centralization was performed in 9 affected limbs, whereas radialization was performed in 8 affected limbs. Nine affected limbs had type 4 RLD, and 8 affected limbs had type 3 RLD. There was no significant difference in the hand-forearm angle in the immediate postoperative period. At 3 months, the radiologic hand-forearm angle increased to 19 degrees in the centralization group, while the radialization group showed an average increase to 4 degrees. This increase in the hand-forearm angle continued at 6-, 12-, and 24-month follow-up assessments. Worsening of the deformity was more in the centralization group, as compared with the radialization group. The forearm length also significantly differed in the 2 groups at 6-, 12-, and 24-month follow-up; however, when adjusted for preoperative lengths, the difference was significant only at 12- and 24-month follow-up. Conclusions: At a short-to-intermediate–term follow-up, radialization fares better than centralization in terms of recurrence of deformity and in terms of affecting the forearm length. Longer follow-up with a larger sample size is needed to draw definitive conclusions. Level of Evidence: Level I. Abstract : Supplemental Digital Content is available in the text.